Cyclic Intermittent Hypoxia Enhances Renal Sympathetic Response To ICV ET-1 In Conscious Rats - Huang, Jianhua (2010)
To test the hypothesis that central changes in sympathoregulation might contribute to sympathoexcitation after cyclic intermittent hypoxia (CIH) we exposed male Sprague-Dawley rats to CIH or to room air sham (Sham) for 8 hours/d for 3 weeks. After completion of the exposure we assessed heart rate, mean arterial pressure and renal sympathetic nerve activity in conscious animals before and after intracerebroventricular (i.c.v.) administration of endothelin-1 (ET-1, 3 pmol). CIH-exposed animals had a significantly greater sympathetic response to ET-1 than did Sham-exposed animals (CIH 137.8 ± 15.6% of baseline; Sham 112.2 ± 10.0 % of baseline; CIH vs. Sham, P = 0.0373). This enhanced sympathetic response to i.c.v. ET-1 was associated with greater expression of endothelin receptor A (ETA) protein in the subfornical organs of CIH-exposed relative to Sham-exposed rats. We conclude that 3-week CIH exposure enhances central ET-1 receptor expression and the sympathetic response to i.c.v. ET-1 suggesting central endothelin may contribute to the sympathetic and hemodynamic response to cyclic intermittent hypoxia.